Variasi Komunikasi Virtual pada Kelompok Pemain Game Mobile Legends - Bella Febriyana Ananda; Zainal Abidin Achmad; Syifa Syarifah Alamiyah; Ahimsa Adi Wibowo; Latif Ahmad Fauzan (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2022)
The Mobile Legends game application has virtual communication features, including Voice Chat, Chatbox, and Quick Chat. This study aims to observe variations of virtual communication used by the Moba Analog Team when playing the game. This study uses a qualitative method with a virtual ethnographic approach. The results show that virtual communication produces a variety of distinctive languages or odes) that is understood and interpreted by members of the Moba Analog Team. A variety of languages with unique codes has been produced due to the virtual conversations intensity and the need for tactics to run the game. Moba Analog Team members play games together almost every night. Virtual communication features facilitate communication between members when acting as a player in the Mobile Legends game. The virtual conversation while playing the games is not merely talking about playing tactics, but it extends to wider topics such as lectures, friendship, family, viral issues on social media, and politics.